The plague : pre-visualisation of visual allegory : adapting a classic novel to film for a modern audience through the lens of mid-twentieth-century existentialism : Master of Design, Massey University, Wellington, New Zealand - Bronswijk, Jack (Massey University, 2022)
Philosophical discourse, even of ubiquitous human questions, is often restricted to academic circles due to its jargon and largely abstract nature, however the use of entertainment is an effective method of conveying complex ideas to a general audience. The use of allegory in entertainment media, such as literature and film, are attempts to simplify complex philosophical thinking by providing tangible examples in the form of stories; something human beings have been utilising for the passing on of knowledge since time immemorial. One such example is French existentialist author Albert Camus’ novel The Plague (Camus, 1947) which explores human desire for individual purpose, and one’s relationship with their own inevitable death, through an allegorical story of a community experiencing a pandemic. There are however, no set rules on how to include such symbolism and allegory in stories. The central obstacle of any writer, artist, or designer is therefore how to most effectively convey the symbolic purpose of characters, settings, and situations to support the central themes and impart the intended message. This dilemma is mirrored in a central problem existentialist philosophy explores which is that of finding purpose within an inherently meaningless universe. Another French existentialist thinker, Jean-Paul Sartre (1905-1980), posed that in a meaningless world “existence precedes essence” (Sartre, 1946, p.20) – that one is not defined by the categories they fall into at birth but rather is tasked with constructing their own identity through action. This notion of definition through action lends itself well to visually communicating complex allegory in film. The intention of this project is to understand the use of allegory in visual art, through the lens of mid-twentieth-century existentialist philosophy, and incorporate these techniques into a practical framework for designing key scenes illustrations and conceptual design work to pre-visualize a film adaptation of a novel. This project demonstrates that the meaningful interaction of subjects, and contextualization of elements, heightens the visual storytelling, and allegorical potential, of the pre-visualization process by adapting the story, and underlying philosophical discussion, of Camus’ The Plague to film for a modern audience.
Keywords: 330316 Visual communication design (incl. graphic design)